Formation of Student Competencies in the Pirls International Assessment Program: A Focus on 4th Grade Pupils - Abdisattarovna, Tashpulatova Janar (European Journal of Life Safety and Stability (2660-9630), 2023)
This article explores the formation of student competencies in the PIRLS International Assessment Program, focusing on 4th grade learners. It highlights the significance of the program in developing reading comprehension skills, language proficiency, critical thinking, and a love for reading among students. The article discusses the impact of the assessment on student development, identifies areas for improvement, and emphasizes the importance of international benchmarking and collaboration. By nurturing competencies early on, students are empowered for future success in academia and beyond.